COVID-19 alcohol availability and suicide rates in South Africa - Hodgson, Anthony (Department of Public Health and Family Medicine, 2024)
Investigations into COVID-19 and suicide have predominantly found no significant evidence of increased suicide rates, but few studies have been conducted in low- and middle-income countries and none in Sub-Saharan Africa. We used data from two nationally representative surveys of post-mortem investigations to estimate changes in suicide rates in South Africa associated with the COVID-19 pandemic and related events. We specifically explored variance in suicide rates coinciding with lockdown stages and periods of alcohol prohibition. We found no significant differences between suicide rates during the pandemic period (April 2020 to March 2021) compared to the prior survey period of 2017, but significant variation within the pandemic period. Periods of alcohol prohibition were protective with an estimated 5.82 [5.78, 5.86] fewer suicide deaths per day compared to periods of no or partial alcohol restriction. This constituted a 30% decrease in expected suicides under normal trading conditions. Cessation of alcohol prohibition had a negative effect and suicide rates during periods of no or partial alcohol restriction were significantly higher than in 2017. We conclude that in South Africa the observed null effect of the COVID-19 pandemic on annual suicide rates masks considerable temporal variation associated with restrictions, and periods of alcohol prohibition in particular.